2011
DOI: 10.1007/s10344-011-0523-0
|View full text |Cite
|
Sign up to set email alerts
|

A study of fox (Vulpes vulpes) visits to farm buildings in Southwest England and the implications for disease management

Abstract: Farm buildings may offer foraging opportunities for wild mammals, which may result in economic losses and the potential for disease transmission to livestock. Effective management to reduce such risks requires knowledge of the behaviour of wildlife visiting buildings. Remote surveillance was used to monitor red fox (Vulpes vulpes) activity in buildings on cattle farms in Southwest England over a period of 2 years. Frequent visits were observed throughout the year, during which foxes excreted and scent-marked o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In France, a study carried out in Côte d’Or based on camera monitoring at 101 points located in pastures and farm buildings and considered attractive for wildlife (water and food access), revealed that the fox is the most frequent wild species to visit these sites compared to badgers and wild ungulates [ 24 , 25 ]. Previous study in England and Ireland also showed that foxes visited cattle buildings very frequently [ 26 , 27 ]. In cattle sheds, foxes were observed predating rodents [ 26 ] but also in feeding troughs [ 25 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In France, a study carried out in Côte d’Or based on camera monitoring at 101 points located in pastures and farm buildings and considered attractive for wildlife (water and food access), revealed that the fox is the most frequent wild species to visit these sites compared to badgers and wild ungulates [ 24 , 25 ]. Previous study in England and Ireland also showed that foxes visited cattle buildings very frequently [ 26 , 27 ]. In cattle sheds, foxes were observed predating rodents [ 26 ] but also in feeding troughs [ 25 ].…”
Section: Discussionmentioning
confidence: 97%
“…Previous study in England and Ireland also showed that foxes visited cattle buildings very frequently [ 26 , 27 ]. In cattle sheds, foxes were observed predating rodents [ 26 ] but also in feeding troughs [ 25 ]. This behaviour can lead to indirect exposure to M. bovis bacilli excreted by cattle.…”
Section: Discussionmentioning
confidence: 97%
“…Bovine tuberculosis transmission is thought to occur primarily through direct contact, but its ability to persist in the environment has raised questions about the role of indirect transmission routes [64,65]. Likewise, wildlife scent marking behavior at the human-livestock interface is of concern since some wildlife species (e.g., foxes, badgers) preferentially use farm food storage buildings for foraging and scent-marking which heightens pathogen transmission risk [66,67]. Scent marking may also influence the success of species reintroductions and population management: introducing translocated animals into an established territorial population may increase transmission risk because of increased overlap in home ranges or direct contacts [68].…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Second, due to our sampling design was composed by passive single-camera stations monitoring restricted areas during delimited periods, it prevented us from better describing social signaling behaviors potentially involved in disease transmission, such as sniffing, rolling, defecating, urinating. According to previous studies, cross-species scent marking could potentially promote the persistence and spread of pathogens released into feces and urine of dogs and foxes interacting at the wildlife-domestic interface [e.g., ( 24 , 43 , 90 , 91 )], which may be mediated by the interplay between prolonged shedding (e.g., CDV) and extended environmental resistance (e.g., CPV) characterizing several multi-host pathogens ( 92 ). Third, because random camera sampling could only record indirect interactions derived from animal movement through the landscape, perhaps the simultaneous monitoring of aggregation points (i.e., known canid paths) by camera trapping, and individual tracking with GPS telemetry or proximity loggers may be alternative approaches to account for more precise dog-fox interaction frequencies and their related temporal patterns ( 93 ).…”
Section: Discussionmentioning
confidence: 99%